Effects of structural planes on the microseismicity associated with rockburst development processes in deep tunnels of the Jinping-II Hydropower Station, China. (February 2019) - Feng, Guang-Liang; Feng, Xia-Ting; Chen, Bing-Rui; Xiao, Ya-Xun; Zhao, Zhou-Neng
Highlights: Microseismicity associated with 44 moderate and intense rockbursts were studied. The structural planes in the areas where rockbursts occur are mostly stiff ones and grade III or IV ones. Structural planes change the microseismicity in the rockbursts development processes. Abstract: Rockbursts cause serious casualties and damage in deep, hard rock tunnels. Structural planes can play an important role in the rockburst development process. In this paper, effects of structural planes on the microseismicity in rockburst development processes are summarized and studied in deep tunnels of the Jinping-II Hydropower Station, China. The study is based on an analysis of 44 moderate and intense rockbursts which occurred during a period of more than a year of microseismic (MS) monitoring and relates to 11.6 km of tunneling. The results show that most of the cases are affected by structural planes regardless of the rockburst's moderate or intense character. The structural planes in the areas where rockbursts occur are mostly stiff ones and grade III or IV ones. In rockbursts development processes affected by structural planes, the MS energy proportion of big MS events, i.e. whose logarithm of MS energy (measured in Joules) is larger than 3.83, is comparatively lower. Structural planes change the way microseismicity evolves. Right from the beginning in the rockburst development and just before the rockburst affected by structural planes, there were some big MS events occurring. And structural planes cause rockbursts to occur more likely. Threshold values of the microseismicity (number of MS events and MS energy) for rockburst occurrence are relatively lower. In addition, the microseismicity in rockburst development processes with different intensities and with/without structural planes shows discreteness and the microseismicity is greater in more intense rockbursts.